The Exploration of Lae Une Folklore and Pakpak Bharat Culture - Sembiring, Yenita Br; Sinurat, Yoyan Riris; Pinem, Feby Radila; Bangun, Kristina; Manalu, Lastri Mariana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The researcher raised the fact that the Pakpak Bharat culture was not widely known as a research problem. This study tries to provide a solution to the problem through written analysis of Pakpak culture which is reflected in the Lae Une folklore. This research utilizes the descriptive qualitative method. Research data was obtained from informants who are natives. The researcher used interviews as a research instrument and then the data collected was analyzed using the content analysis method. The result of the research is the complete text of the Lae Une folklore and its cultural analysis. Researchers found the potential of culture in teaching in various related and unrelated fields in language, thus confirming the theoretical basis presented at the beginning of the study.